Heterogeneity in fibroblast proliferation and survival in idiopathic pulmonary fibrosis - Habiel, David M.; Hogaboam, Cory (Frontiers in Pharmacology, 2014)
Idiopathic pulmonary fibrosis (IPF) is the most common form of interstitial lung disease characterized by the persistence of activated myofibroblasts resulting in excessive deposition of extracellular matrix proteins and profound tissue remodeling. Myofibroblasts have been shown to arise from interstitial fibroblasts, epithelial to mesenchymal transition of type II alveolar epithelial cells, and the differentiation of recruited fibrocytes. There are many mechanisms that are utilized by these cells for survival, proliferation and persistent activation including up-regulation of cytokines (i.e. Interlukin 6 (IL-6)), cytokine receptors (i.e. Interlukin 6 Receptor 1 (IL-6R1), Glycoprotein 130 (gp130) and C-C Chemokine Receptor type 7 (CCR7) and innate pattern recognition receptors (PRRs; i.e. Toll Like Receptor 9 (TLR9)). In this review, we will discuss the role of the cytokines IL-6 and CCL21, their receptors and the pattern recognition receptor (PRR), TLR9, in fibroblast recruitment, activation, survival and differentiation into myofibroblasts in IPF.